The way of sensation: Notes on the aesthetics of painting in Merleau-Ponty - Fagioli, Nicolás (2025)
In this writing, we delve into some of Merleau-Ponty’s considerations regarding painting. The exploration will be guided by the notion of sensation, a concept that the philosopher adopts from the French painter Paul Cézanne. The aim is to elucidate how the author finds, in Cézanne and in modernist painting in general, a pathway to construct a new conception of sensory experience. This conception will be central to the philosopher’s later reflections, particularly those in which the ontological aspect of his philosophy is emphasized, mainly developed in The Visible and the Invisible.